The Effect of Strategic Intelligence on Enhancing Customer Value: An Exploratory Study of the Opinions of a Sample of Employees at the State Company For Drug And Medical Supplies Manufacturing / Samarra - Iraq - Abdul-Razzaq, Maha Mohammed; Turki, Mona Demak (Journal of Ecohumanism, 2024)
The core objective of this research was to pinpoint the sources of strategic intelligence and their effect upon enhancing customer value, as well as to provide some suggestions that contribute to clarifying the effect between the research variables. Accordingly, the current problem was represented by the central question: (Is there a statistically significant effect of strategic intelligence on enhancing customer value?). To assess the opinions of the respondents, the research relied on the descriptive-analytical approach in dealing with the theoretical and field data of the studied company. Several research tools were used in the field aspect of the study to achieve the desired results, with the questionnaire being the main tool for data collection. A total of 130 forms were given to a random sample of employees in the studied company, of which 125 valid forms were returned for analysis, representing a rate of 96%. Several statistical methods and tools were used to handle the data, analyze the questionnaire items, and test its hypotheses based on the data processed through the (SPSS.V26) statistical program. The research concluded with several findings, including there is a statistically significant positive effect of strategic intelligence on enhancing customer value in the studied company.